Energy Harvesting in the Crane-Hoisting Mechanism - Tomasz Haniszewski; Maria Cieśla (Energies, 2022)
The subject of the model research contained in this paper is an application of a motion energy–harvesting device on a crane-hoisting mechanism to power independent measurement devices. Numerical experiments focused on the selected motion energy–harvesting device (M-EHS) and its configuration properties in the context of energy-harvesting efficiency in the case of using it on a crane. The results of the computer simulations were limited to the initial specified conditions for the harvester and the movement of the conditions of the crane-hoisting mechanism. The article compares the energy efficiency for the selected construction and parameters of the harvester for specific hoisting speed and the arm length of the motion conversion system. For this purpose, the initial conditions for the crane and the configuration of parameters of the energy harvester were assumed. The results are visualized on the diagram of RMS voltage induced on piezoelectric elements, showing the impact of individual solutions of the proposed motion energy–harvesting device on the efficiency of energy harvesting. The results of the efficiency of the simulations show that the motion harvester ranges from 0.44 V to 14.22 V, depending on the speed of the crane-hoisting mechanism and the length of the arm of the motion conversion system. Still, the design allows for an adjustment to the given conditions by tuning up the M-EHS to a specified excitation frequency and working conditions.